Kinemaster-Based Video Media Development On Integrated Thematic Learning In Elementary School - Erita, Yeni; Hervia, Silvia; Febria, Bunga; Ismail, Kamarul Bin (JOURNAL OF DIGITAL LEARNING AND DISTANCE EDUCATION, 2022)
This research is motivated by the lack of availability of IT-based learning media that can motivate and attract students' interest in learning. Thus, students are less interested and find it difficult to understand the learning material. This study aims to develop KineMaster learning media for integrated thematic learning that is valid and practical. This research is development research (R&D) with the ADDIE development model. The results of this study indicate that the resulting learning media reach a validity level of 91.25% for the material, 86% for language, and 87% for media with a valid category. The level of practicality by teachers is 86% in the practical category, and the level of practicality by students is 92% in the practical category. Thus, it can be concluded that the KineMaster-based learning media in integrated thematic learning in grade IV SD has been declared valid and practical for use in learning.